THE EFFECT OF INFLATION, EXPORT-IMPORT AND INTEREST RATES ON SALES THROUGH GDP/GDP MODERATION VARIABLES - Akbar, Taufik - (Journal of Management and Leadership, 2023)
This study aims to determine the effect of inflation, export-import, interest rates on sales in state-owned pharmaceutical holding companies with moderating variables of Gross Domestic Product (GDP). The type of research used is quantitative with primary and secondary data sources related to inflation, export-import, interest rates, GDP and sales. The data used is a combination of time series data for 2018-2022 and cross-section which is then referred to as panel data. The study was also conducted in more depth using a research instrument in the form of a questionnaire with respondents as many as six people who had positions as department heads in the parent company of Pharmaceutical SOEs. Data analysis techniques use multiple linear regression analysis and Moderating Regression Analysis. The results showed that simultaneously the variables of inflation, export-import and interest rates had a positive and significant effect on sales. Meanwhile, the moderation variable, namely GDP, partially affects sales, but cannot moderate the influence of inflation and export-import both in terms of strengthening and weakening the influence of the independent variable on the dependent variable. Other research results show GDP can be a pure moderator of the influence of interest rates on sales. This research has limitations, namely the variables used are macro, therefore for future research it is expected to be able to conduct research using micro variables in the economy. Keywords: Inflation, Export-Import, Interest Rate, GDP, Sales and Holding Company of SOEs.